2023
DOI: 10.1002/rfc2.24
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and knowledge about HPV vaccination among Ghanaian women with cervical cancer

Abstract: Objective To explore knowledge about the human papillomavirus (HPV), HPV vaccination, barriers to vaccination and acceptance of the HPV vaccine in the highest‐risk and most‐impacted population in Ghana. Methods A survey was administered to 100 women with histologically confirmed cervical cancer at a teaching hospital in Ghana. Results Participants had a mean age of 59 (±14.3) years, 65.0% had a parity of five or higher and 89.0% had a monthly income less than 500 Ghana cedis ($63 USD). Seventy‐nine percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Insufficient knowledge about cervical cancer risk factors, HPV vaccination, and screening is linked to low participation in prevention programs and adverse health outcomes including late diagnosis and treatment (Chidyaonga-Maseko et al, 2015;Ebu et al, 2014;Rugutt, 2014). While previous studies have found inadequate knowledge about cervical cancer risk factors, vaccination, and screening among Ghanaian women, men in the general population, and college students (Binka et al, 2016;Ebu et al, 2014;Gyamfua et al, 2019;Williams & Amoateng, 2012;Zurales et al, 2023), few studies have examined knowledge of the disease among high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient knowledge about cervical cancer risk factors, HPV vaccination, and screening is linked to low participation in prevention programs and adverse health outcomes including late diagnosis and treatment (Chidyaonga-Maseko et al, 2015;Ebu et al, 2014;Rugutt, 2014). While previous studies have found inadequate knowledge about cervical cancer risk factors, vaccination, and screening among Ghanaian women, men in the general population, and college students (Binka et al, 2016;Ebu et al, 2014;Gyamfua et al, 2019;Williams & Amoateng, 2012;Zurales et al, 2023), few studies have examined knowledge of the disease among high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, following the introduction of the HPV vaccine in Ghana in 2013 through support from the Global Alliance for Vaccines and Immunisations (GAVI), vaccination remains low. Poor access, lack of knowledge and cost have been reported as barriers to uptake [ 22 ]. The estimated population of all women that have been screened by pap smear is low at 2.4%, most of which has been opportunistic [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%